Prevalence of apical periodontitis and quality of root canal treatment in an adult Kuwaiti sub-population: a cross-sectional study - Abdulrahman A. Alhailaa; Saad A Al-Nazhan; Mazen A Aldosimani (Restorative Dentistry & Endodontics, 2024)
ObjectivesThis cross-sectional study evaluated the prevalence of apical periodontitis (AP) and the technical quality of root canal fillings in an adult Kuwaiti subpopulation using cone-beam computed tomography (CBCT) images.Materials and MethodsTwo experienced examiners analyzed 250 CBCT images obtained from Kuwaiti patients aged 15–65 years who attended government dental specialist clinics between January 2019 and September 2020. The assessment followed the radiographic scoring criteria proposed by De Moor for periapical status and the technical quality of root canal filling. Chi-square and Fisher’s exact tests were used for statistical analysis, with significance level set at p < 0.05.ResultsAmong the 2,762 examined teeth, 191 (6.91%) exhibited radiographic signs of AP, and 176 (6.37%) had undergone root canal filling. AP prevalence in root canal-treated teeth was 32.38%, with a significant difference between males and females. Most of the endodontically treated teeth exhibited adequate root canal filling (71.5%).ConclusionsThe study demonstrated a comparable prevalence of AP and satisfactory execution of root canal treatment compared to similar studies in different countries.